Characterization of an X‐ray mirror mechanical bender for the European XFEL. (31st May 2016) - Vannoni, Maurizio; Freijo Martín, Idoia; Sinn, Harald
Abstract : An X‐ray mirror mechanical bender is characterized. The device is measured using a Fizeau large‐aperture interferometer, and the most important effects, such as hysteresis, twisting, reproducibility and stability are investigated. The mirror silicon substrate is 950 mm long and the system is a possible candidate for the `adjustable' mirror element foreseen in the optical setup of the European XFEL beam transport. Abstract : One of the classical devices used to tune a mirror on an X‐ray optical setup is a mechanical bender. This is often designed in such a way that the mirror is held with clamps on both ends; a motor is then used to put a torque on the clamps, inducing a cylindrical shape of the mirror surface. A mechanical bender with this design was recently characterized, to bend a 950 mm‐long mirror up to a radius of curvature of 10 km. The characterization was performed using a large‐aperture Fizeau interferometer with an angled incidence setup. Some particular and critical effects were investigated, such as calibration, hysteresis, twisting and long‐term stability.